2015
DOI: 10.4103/0974-7753.171566
|View full text |Cite
|
Sign up to set email alerts
|

Is early onset androgenic alopecia a marker of metabolic syndrome and carotid artery atherosclerosis in young Indian male patients?

Abstract: Background:Androgenic alopecia (AGA) is a common cosmetically and psychosocially distressing condition. High androgen level contributes to the development of atherosclerosis, thrombosis leading to hypertension and hypercholesterolemia.Objectives:To study the clinico-epidemiological profile of AGA and the presence of metabolic syndrome (MetS) and carotid artery atherosclerosis in male patients with early onset AGA as compared to controls.Materials and Methods:In this case-control study, 100 male patients of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 50 publications
2
22
2
2
Order By: Relevance
“…In 2000 Matilainen et al observed early AGA associated with increased insulin resistance [ 60 ]. A case control study of 100 young male patients conducted by Banger et al detected a statistically significant difference regarding the number of individuals in the group of AGA fulfilling the criteria for MeTS in comparison with the control group [ 61 ]. The study by El Sayed et al among 90 female patients with AGA showed a statistically significant increase in the incidence and severity of female pattern hair loss especially in relation to hypertension and obesity (defined by NCEP-ATP III criteria) [ 62 ].…”
Section: Sebaceous and Apocrine Glands Disordersmentioning
confidence: 99%
“…In 2000 Matilainen et al observed early AGA associated with increased insulin resistance [ 60 ]. A case control study of 100 young male patients conducted by Banger et al detected a statistically significant difference regarding the number of individuals in the group of AGA fulfilling the criteria for MeTS in comparison with the control group [ 61 ]. The study by El Sayed et al among 90 female patients with AGA showed a statistically significant increase in the incidence and severity of female pattern hair loss especially in relation to hypertension and obesity (defined by NCEP-ATP III criteria) [ 62 ].…”
Section: Sebaceous and Apocrine Glands Disordersmentioning
confidence: 99%
“…Androgenetic alopecia (AGA) is the most common cause of hair loss. [ 1 2 ] Although it is a medically benign condition, it can have a significant psychosocial impact on patients. It is a very common condition encountered in almost all dermatology outpatient departments across the world.…”
Section: Introductionmentioning
confidence: 99%
“…A population-based study in India of 1005 participants showed 58% AGA in males aged 30–50 years. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%
“…A higher number of articles investigating the metabolic profile was found compared to those investigating the hormonal status. We did not considered in the meta-analysis the total testosterone levels of the study by Banger and colleagues 22 and the SHBG levels of the study by Gonzalez-Gonzalez and colleagues 9 , since they were not comparable with those of the other studies. We unsuccessfully tried to get in touch with the authors.…”
Section: Resultsmentioning
confidence: 99%
“… 21 India, single institution 85 85 ≥I 26.44 [2.64] 25.65 [3.19] Blood pressure, FBS, HOMA-index, total-C, HDL-C, LDL-C, VLDL, triglycerides, BMI *** * *** Moderate Banger et al . 22 India, single institution 100 100 ≥I 27.03 [5.36] 26.22 [5.1] Blood pressure, FBG, total-C, HDL-C, LDL-C, triglycerides, BMI, WC, WHR, CRP, ESR **** * *** Low Sanke et al . 23 India, single institution 57 32 ≥III 24.7 [2.8] 24.2 [2.6] FBS, insulin, HOMA-index, BMI, LH, FSH, LH/FSH ratio, total testosterone, FAI, DHEAS, SHBG, **** * *** Low Abbreviations: AGA = androgenetic alopecia; BMI = body mass index; CRP = C-reactive protein; DHEAS = dehydroepiandrosterone sulphate; ESR = erythrocyte sedimentation rate; FAI = free androgen index; FBS = fasting blood sugar; FIRI = fasting insulin resistance index; HDL-C = HDL cholesterol; LDL-C = LDL cholesterol; SHBG = sex hormone binding globulin; total-C = total cholesterol; VLDL = very low-density lipoproteins; WC = waist circumference; WHR = waist to hip ratio.…”
Section: Methodsmentioning
confidence: 99%